Implementation of the data encryption using caesar cipher and vernam cipher methods based on CrypTool2 - Salmi, Gading Nur; Siagian, Farhan (Journal of Soft Computing Exploration, 2022)
Information has become precious and essential for all fields, so it is crucial to carry out information security. The principle of information security is to protect and safeguard information with the aim that the information is not entitled to be read, modified, or deleted by anyone who does not have rights to it. The purpose of our research is to analyze how the caesar cipher and vernam cipher methods are jointly used in the cryptographic process and are expected to produce a high level of data encryption so that it can increase the security of data or messages. The research applies the combination of the caesar cipher and vernam cipher methods to encrypt text data or messages. Using the secret key value will convert the input message into an encrypted message that is difficult to crack and cannot be decrypted again. The input text and the encrypted data have no resemblance to maintain the confidentiality of the information or data contents.